Quantitative evaluation of water content in composite honeycomb structures by using one-sided IR thermography: is there any promise?; Proceedings of SPIE; Vol. 10214 : Thermosense: Thermal Infrared Applications XXXIX - Chulkov A. O. Arseniy Olegovich; Vavilov V. P. Vladimir Platonovich; Moskovchenko A. I. Aleksey Igorevich; Pan Yanyan (2017, 2017)
Title screen